Birokratisasi Pernikahan - Muhazir (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2021)
Marriage outside the KUA becomes polemic in itself when the culture that is considered alms by the community is different from the state's point of view. The wedding procession is a value in itself for the community so that the wedding procession is sometimes accompanied by customs and traditions so that the sacredness in marriage is seen and can be felt. This paper is an empirical study with a sociological approach. This approach is carried out to see and analyze the legal, cultural and social aspects of the practice of marriage processions carried out by the people of Malang City. This paper argues that the majority of residents prefer to hold a marriage contract outside the KUA. This is influenced by several factors, first; the sacred factor; Second, the ease of implementation factor; third, elements of customs and culture; fourth, avoiding bad prejudice from the community, so that many residents prefer to carry out the marriage contract outside the KUA rather than at the KUA.